Spectral Domain-Optical Coherence Tomography As a New Diagnostic Marker for Idiopathic Normal Pressure Hydrocephalus - Afonso, Joana M.; Falcão, Manuel; Schlichtenbrede, Frank; Falcão-Reis, Fernando; Silva, Sérgio Estrela; Schneider, Till M. (Frontiers in Neurology, 2017)
Purpose Characterized by a progressive onset of gait disturbances, dementia and urinary incontinence, idiopathic Normal Pressure Hydrocephalus (iNPH) is considered a rare but under-diagnosed disease. Non-invasive diagnostic markers are still insufficient to enable the diagnosis of iNPH with certainty and yet early treatment with ventriculoperitoneal (VP)-shunting can reverse symptoms and stop disease progression. Vascular circulation abnormalities in iNPH may be reflected by changes in subfoveal and peripaillary choroidal thickness. This study uses spectral domain - optical coherence tomography (SD-OCT) based measures of retinal and choroidal thickness to test this hypothesis and to assess ophthalmological non-invasive markers for iNPH. Methods 12 patients that displayed neurological and neuroradiological characteristics of iNPH were subject to a full ophthalmological examination including enhanced depth imaging (EDI) SD-OCT. Of the 12 included iNPH patients 6 had undergone VP-shunting with beneficial outcome. Parameters studied with EDI SD-OCT were macular retinal thickness (MT), subfoveal choroidal thickness (SFChT), retinal nerve fiber layer thickness (RNFL) and peripapillary choroidal thickness (PPChT). Results were compared with 13 healthy, age-matched controls. Results RNFL and MT values of iNPH patients did not reflect atrophy. Non-shunted iNPH patients showed significantly lowered median PPChT and SFChT values compared to healthy controls. Shunted iNPH patients displayed a significantly higher median PPChT and SFChT compared to non-shunted iNPH patients. SFChT and PPChT values in shunted patients were not significantly different to values in healthy controls. Conclusion Although limited by small sample size, SD-OCT measures in this study reveal significant changes of choroidal thickness and support the hypothesis of choroidal susceptibility to hemodynamic alterations in iNPH. Non-shunted iNPH patients in this study show choroidal thinning in combination with normal RNFL and MT values. In addition to neurological and neuroradiological exams this pattern may aid in the challenging diagnosis of iNPH.